Entanglement - Gržinić, Marina (Identities: Journal for Politics, Gender and Culture, 2013)
My intention is to expose the way in how gender, class and race and media were and are overdeterminated, but without falling into a simplification that they are simply “contradictory.” I will make recourse to some contemporary performative practices and political spaces in Europe that dismantles the singular established contemporary history of art and performative practices in European context. Author(s): Marina Gržinić Title (English): Entanglement Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 7-13 Page Count: 7 Citation (English): Marina Gržinić, “Entanglement,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 7-13.